Syriac Apocalyptic and the Body Politic: from individual salvation to the Fate of the State. Notes on Seventh Century Texts - Ubierna, Pablo Alejandro (2012)
One of the main goals of this paper is to comment on the eschatological notion of “end” as found in a Syriac apocalyptic text of the seventh century, the Syriac Apocalypse of Daniel (or Pseudo-Daniel), recently edited by Matthias Henze and the possible links with the canonical tradition related to the Book of Daniel in the Syriac Bible and to present its own specificity due to the eschatological tone that relates the text with the classical authors of the fourth century like Aphraat. This eschatological tone marks a distance with other Syriac texts of the seventh century with a more political approach. .